2017
DOI: 10.11144/javeriana.upsy16-2.iein
|View full text |Cite
|
Sign up to set email alerts
|

Construcción del cuestionario de intención hacia el alcohol para niños mexicanos desde la Teoría de la Conducta Planeada.

Abstract: El incremento en el consumo de alcohol y la disminución en la edad de inicio requiere del desarrollo de propuestas preventivas dirigidas a población en edad más temprana, sustentadas teórica y empíricamente. La Teoría de la Conducta Planeada (TCP) constituye una base sólida para el desarrollo de propuestas de intervención en prevención de un comportamiento, para ello se debe conocer la intención que tiene el sujeto de realizarlo, siendo necesario evaluar sus creencias de comportamiento, normativas y de control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
1
0
2
Order By: Relevance
“…The TPB sets forth that human behaviors are reasoned or planned actions, as they are consistent with a person's beliefs (26). In this sense, it can be asserted that it is through behavioral beliefs that people weigh the consequences of future actions in terms of their favorable or unfavorable nature (21).…”
Section: Discussionmentioning
confidence: 99%
“…The TPB sets forth that human behaviors are reasoned or planned actions, as they are consistent with a person's beliefs (26). In this sense, it can be asserted that it is through behavioral beliefs that people weigh the consequences of future actions in terms of their favorable or unfavorable nature (21).…”
Section: Discussionmentioning
confidence: 99%
“…En la medición de las actitudes se obtuvieron tres factores: Importancia de la creencia (Probar cerveza cuando tenga un problema es); Evaluación de la creencia (Probar cerveza para calmarme cuando estoy enojado es) y Evaluación de la creencia positiva o negativa (Probar cerveza para relajarme es). Obtuvieron un Alpha de .88 y una varianza explicada de 56%, sin embargo, su uso es para población infantil (Hernández Chávez et al, 2017).…”
Section: Introductionunclassified
“…In Mexico, various investigations have reported the occurrence of experimental consumption in children of primary education, such as the one carried out in Celaya, Guanajuato, with 39 children of the first grade of primary education, aged 6 and 7, it was identified that 30.6% He had already had a beer sometime in his life. These types of findings demand preventive actions directed at school children (Hernández, et al 2017).…”
Section: Introductionmentioning
confidence: 99%